A Note on the Global Stability of a Simple Growth Model With Many Capital Goods - Burmeister, Edwin; Dobell, Rodney; Kuga, Kiyoshi (Quarterly Journal of Economics, 1968)
I. Introduction, 657. — II. The model, 658. — III. Reduction of the system, 660, — IV. The accumulation equations, 660. — V. Global stability, 660. — Appendix, 664.